Occlusal plane inclination in children between 9 and 10 years of age with postural asymmetry: a study on the frontal plane - Rebolledo-Uribe, Juan Pablo; Pincheira-Barbé, Patricio Andrés; Bittner-Schmidt, Verónica; Frugone-Zambra, Raúl Ernesto (Revista Facultad de Odontología Universidad de Antioquia, 2012)
Introduction: with the purpose of establishing the relationship between side and direction of occlusal plane inclination in children with postural asymmetry of the suprascapular unit, an observational study was conducted in 34 subjects aged 9 to 10 years. Methods: both postural asymmetry and occlusal plane inclination using a fox plate were measured by means of photograph analysis standardized with the Kinovea 0.7.10 software version 2. Results: 18 subjects presented a minor occipital middle cervical-scapular waist angle (MOMCSWA) to the left, with a minimum angle of 87.4º; 4 of them presented elevated occlusal plane (EOP) in the same side in relation the bipupillary plane; in 11 patients this plane was elevated to the right, and 3 did not present occlusal plane inclination. 16 of the subjects presented (MOMCSWA) to the right with a minimum angle of 87.13º; 5 of them showed EOP to the same side, in 7 patients the plane was elevated to the left, and 4 did not present occlusal plane inclination. The variables used were average and standard deviation. Conclusion: this study allowed concluding that healthy kids with postural asymmetry present a tendency to have a lower occlusal plane to the side of head inclination, probably due to factors related do dentoalveolar growth.